The Role of Administrative Empowerment in Organizational Effectiveness: Pilot Study in the Applied Research Unit in Renewable Energies in Ghardaia - Dine, Smail; lamour, sohila (Finance and Business Economies Review, 2022)
This study discussed the role of administrative empowerment in organizational effectiveness in the enterprise under study-Ghardaia , and to achieve this, a questionnaire was designed and distributed to the employees of the studied institution،were used statistical packages for social sciences spss la analyze the questionnaire data and testing of hypotheses. The study found an effect of experience on organizational effectiveness, as it was found that there is an inverse relationship between delegation of authority and organizational effectiveness, as well as the absence of an effect of training on organizational effectiveness in the studied institution. It recommended the necessity of adhering to social responsibility and focusing oversight on private matters only to achieve greater organizational effectiveness